Metacyclic Trypanosoma vivax possess a surface coat - Gardiner, Peter R.; Webster, P.; Jenni, L.; Moloo, S.K. (Cambridge University Press, 1986)
Coated metacyclics ofTrypanosoma vivaxexist in the hypopharynges of infected tsetse flies and are extruded in low numbers when the flies are induced to probe onto warm slides or into medium. After extensive searching ofT. vivax-infected proboscides, and resort to a process for the examination of single, extruded, metacyclic trypanosomes, electron micro scopic evidence is presented that, contrary to an earlier report, metacyclicT. vivaxacquire a surface coat before contact with the mammalian host. SinceT. vivaxexhibits antigenic variation, the role of the surface coat in this species is likely to be functionally equivalent to the surface coat of the other tsetse-transmitted trypanosome species,T. bruceiandT. congolense.